Principal Functions of Nonselfadjoint Discrete Dirac Equations with Spectral Parameter in Boundary Conditions - Aygar, Yelda; Olgun, Murat; Koprubasi, Turhan (Wiley, 2012)
Let L denote the operator generated in ℓ2(ℕ, ℂ2) by , , n∈ℕ, and the boundary condition , where (an) , (bn), (pn), and (qn) , n∈ℕ are complex sequences, γi, βi∈ℂ , i = 0,1, and λ is an eigenparameter. In this paper we investigated the principal functions corresponding to the eigenvalues and the spectral singularities of L.
Keywords: QA1-939; Discrete version of topics in analysis; nonselfadjoint discrete Dirac equations; Mathematics